Comparison of single and double stage regenerative organic rankine cycle for medium grade heat source through energy and exergy estimation - Ghalya Pikra; Nur Rohmah (International Journal of Renewable Energy Development, 2019)
Regenerative organic Rankine cycle (RORC) can be used to improve organic Rankine cycle (ORC) performance. This paper presents a comparison of a single (SSRORC) and double stage regenerative organic Rankine cycle (DSRORC) using a medium grade heat source. Performance for each system is estimated using the law of thermodynamics I and II through energy and exergy balance. Solar thermal is used as the heat source using therminol 55 as a working fluid, and R141b is used as the organic working fluid. The initial data for the analysis are heat source with 200°C of temperature, and 100 L/min of volume flow rate. Analysis begins by calculating energy input to determine organic working fluid mass flow rate, and continued by calculating energy loss, turbine power and pump power consumption to determine net power output and thermal efficiency. Exergy analysis begins by calculating exergy input to determine exergy efficiency. Exergy loss, exergy destruction at the turbine, pump and feed heater is calculated to complete the calculation. Energy estimation result shows that DSRORC determines better net power output and thermal efficiency for 7.9% than SSRORC, as well as exergy estimation, DSRORC determines higher exergy efficiency for 7.69%. ©2019. CBIORE-IJRED. All rights reserved